A graph-based cloak algorithm to preserve location privacy in location-based services. (2015) - Shanthi, P.; Balasundaram, S.R.
Location-based services (LBS) are context aware systems that facilitate users in terms of providing services such as finding places, routes, ATMs etc. Using the location-context, the service provider can determine the living style, personal details and also, can track an individual. This violates the privacy of the user. Hence, the location-context must be protected from the service provider. Numerous techniques have been proposed by researchers to protect the location-context from malicious LBS providers. Cloaking is an often used technique to protect the location. In this view, this paper focuses on graph-based clique cloak algorithm that aims to find out the maximum clique to form the cloaked region within the maximum area provided by the user. In this approach, the probability of finding the exact user is decreased for the malicious LBS providers and the number of users getting cloaked is increased compared to the other clique cloak algorithms.